A Descriptive Study on Speech Styles Used by Ted Talks’ Speakers on Education - Salem, Irma; Marpaung, Tiarma; Kamengko, Daniel Frengky (English Education Study Program - Artha Wacana Christian University, 2025)
A person can use multiple speech styles at the same time and place. Social factors influence a person or group’s speech style. In this study, the researchers investigated the speech styles used by TED Talks speakers of educational speech and the social factors influencing the speech styles. Documentary was used as research instrument by randomly taking TED Talks videos of the chosen speakers and the speech transcriptions. The researchers analysed the data using Martin Joos’ theory of speech styles and Janet Holmes’s social factors theory. The findings found three types of speech style; 1) formal style, 2) consultative style; and 3) casual style. Formal style was dominantly used in the speeches. From the results, the researchers concluded that speakers commonly use formal style in their speech to suit their academic topics.